A CLINICAL STUDY OF SURGICAL MANAGEMENT OF OLECRANON FRACTURES - Dr. Nitin Jeenjwadia; Dr. Raghvendra Choubisa; Dr. Dinesh Kumar Meena; Dr. A.K. Mehra (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background and Objective: Olecranon fractures are one of the most commonly seen orthopaedic injuries in emergency room. Fractures of the Olecranon typically occurs as a result of RTA, a fall or assault. The accepted management for Olecranon fractures is for non displaced fractures short immobilization followed by gradually increasing range of motion. When displaced, open reduction and internal fixation with k-wire and figure of eight tension band wiring for simple transverse fractures and Olecranon plate for comminuted fractures. The present study is undertaken to evaluate the result of surgical management, the merit and demerits and to asses elbow joint motion and stability after the procedure.Material and Methods: It is a prospective study which was carried out from August 2019 to November 2020 in Maharana Bhupal General Hospital attached to RNT Medical College, Udaipur. In this study period 25 case of fracture Olecranon treated by Tension band wiring with K-wire for simple transverse fracture and Olecranon plate for communited fractures.Results: In our series, majority of patients were males, middle age with RTA being the commonest mode of injury. Most of the cases were Type || B fractures I.e., oblique and transverse fractures according to Colton‟s classification. Surgery was performed with in 4.76 average days. Union was noted clinically, radiologically and functional evaluation was done by Mayo elbow performance score. Excellent results was present in 19(76%) patients, 4(16%) good and 2(8%) fair with no poor result.Conclusion: From the present study it is concluded that the technique of open reduction and internal fixation with K-wire and tension band wiring for simple transverse and oblique fractures and Olecranon plate for comminuted fractures are effective means and gold standard technique of treating fracture of Olecranon and is based on sound biomechnical principal.